A crustal-scale integrated geophysical and tectonic study of the Snake River Plain region, northwestern U.S.A. Issue 15 (18th November 2017) - Khatiwada, Murari; Keller, G. Randy
ABSTRACT: The Pacific Northwest region of North America is a site of very complex tectonomagmatic activity. This activity is due to subduction of the Pacific plate, the associated Cascade chain of volcanoes, micro-plate interactions, and mantle plume activity to the east of the plate margin that produced the Yellowstone hotspot track along the Eastern Snake River Plain (ESRP). A number of recent geophysical and geological studies have produced new results that have drawn attention to the complex tectonic setting of the region east of the Cascade Range, and its tectonic evolution is the subject of considerable scientific interest and debate. Numerous seismic studies have specifically focused on the crustal and upper mantle structure of the ESRP and Yellowstone area. However, crustal-scale studies of the Western Snake River Plain (WSRP) are limited. We undertook an integrated analysis of new and existing geophysical data and geologic constraints to study the crustal structure of the WSRP and generated two-dimensional crustal models across it. We observed both differences and similarities in the structural and tectonic evolution of the eastern and western arms of the SRP based on our integrated analysis. From a broader perspective based on recent geological and geophysical studies in the surrounding region, the intersection of the two arms of the SRP emerges as a major element of a complex tectonic intersection that includes the High Lava Plains of eastern Oregon, the Northern Nevada rift, a southwestern extension of the ESRP into northern Nevada, as well as, faulting and volcanism extending north-westward to connect with the Columbia River basalt plateau region. Thus, the goal of this study is to advance our understanding of the tectonomagmatic evolution of the region and to encourage further studies in the region.